Integrated pest management : potential, constraints and challenges - Koul, Opender; Dhaliwal, G. S.; Cuperus, Gerrit W. (CABI Pub., 2004)
This book addresses many of the key issues surrounding integrated pest management (IPM), particularly of insects. Topics include the pesticide paradox in IPM; risk-benefit analysis; transgenic crops in IPM; and consumer response to IPM. This book will be of great use to researchers in crop protection, entomology and pest management.